Early Detection of Silent Diseases through Health Education and Medical Check-ups in Parakan Village, Garut - Genialita Fadhilla; Hannina Lidina Hanifa; Sitti Fatimah P.H; Nurhabibah Nurhabibah; Dang Soni; Doni Anshar Nuari (Fakultas Kewirausahaan Universitas Garut, 2026)
Non-communicable diseases (NCDs) such as hypertension and diabetes mellitus are silent diseases that often remain undetected in their early stages but may lead to serious complications. Limited public knowledge and restricted access to healthcare services in rural areas, including Parakan Village, Samarang District, Garut Regency, pose challenges for early detection of NCDs. This community service program aimed to improve public knowledge and awareness of silent diseases through health education and simple medical examinations. The activity was carried out in Parakan Village involving 55 adult and elderly participants at risk of NCDs. The methods included interactive health education on silent diseases, simple medical examinations (blood pressure, blood glucose, uric acid, and BMI), as well as medication provision and counseling by healthcare professionals and pharmacists. Knowledge evaluation using pre-test and post-test showed an increase in the average score from 63 to 85 (+22 points; ±34.9%). These results indicate that health education and medical examinations are effective in improving community understanding while supporting early detection and prevention of NCDs, particularly silent diseases, at the community level.